Insight into the adhesion propensities of extracellular polymeric substances (EPS) on the abiotic surface using XDLVO theory. Issue 6 (December 2021) - Ji, Cheng-cheng; Zhou, Hu; Deng, Shao-Kang; Chen, Ke-Yu; Dong, Xiang-Yu; Xu, Xin-Hua; Cheng, Li-Hua
Abstract: The adhesion of microorganisms is ubiquitous and plays a central role in a wide spectrum of problems, including biomedical study, industrial application and environmental microbiology. To know more about mechanisms underlying microalgal early-stage adhesion, the soluble EPS (sEPS) and the bound EPS (bEPS) of Chlorella vulgaris were extracted and characterized for their adhesion behaviors on the hydrophilic polymethyl methacrylate (PMMA) and the hydrophobic polytetrafluoroethylene (PTFE) surfaces in this work. It was found that the sEPS and the bEPS were dominated by hydrophilic fractions (57.6%) and hydrophobic fractions (49.6%) respectively. As a result, the bEPS always showed a higher adhesion propensity than the sEPS, and its adhesion on PTFE was more significant than that on PMMA. According to the extended Derjaguin-Landau-Verwey-Overbeek (XDLVO) theory, the adhesion behavior was dominated by the Lewis acid-base interfacial free energy ( ∆ G mwf AB ) of algal EPS. The bEPS could promote adhesive propensity of both two materials, whereas the sEPS would repulse the hydrophilic surfaces. Additionally, the dissolved organic carbon (DOC) was shown to be a more suitable index for the description of EPS adhesion. This work presents evidence on the mechanisms of the EPS-mediated adhesion process in algal biofilm formation. Graphical Abstract: ga1 Highlights: The sEPS and bEPS of C . vulgaris were dominated by hydrophilic and hydrophobic fractions respectively. The bEPS contained more LMW (< 1 k Da) fraction and was more likely to adhere on the abiotic surface than the sEPS. The bEPS would promote adhesive propensity, whereas the sEPS would repulse the hydrophilic surfaces. The DOC parameter was more suitable for the description of EPS adhesion behaviors.